2014
DOI: 10.1371/journal.pone.0103309
|View full text |Cite
|
Sign up to set email alerts
|

Phase Differences in Expression of Circadian Clock Genes in the Central Nucleus of the Amygdala, Dentate Gyrus, and Suprachiasmatic Nucleus in the Rat

Abstract: We performed a high temporal resolution analysis of the transcript level of two core clock genes, Period2 (Per2) and Bmal1, and a clock output gene, Dbp, in the suprachiasmatic nucleus (SCN), the master circadian clock, and in two forebrain regions, the lateral part of the central nucleus of the amygdala (CEAl), and dentate gyrus (DG), in rats. These regions, as we have shown previously, exhibit opposite rhythms in expression of the core clock protein, PERIOD2 (PER2). We found that the expression of Per2, Bmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 25 publications
2
46
0
Order By: Relevance
“…In the present study, peak expression of PER1 was found at ZT10 and peak expression of PER2 at ZT15 in the SCN, in agreement with results in the mouse [24] and Lewis rats, where peak expression of PER2 occurred in the early part of the dark phase [5]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study, peak expression of PER1 was found at ZT10 and peak expression of PER2 at ZT15 in the SCN, in agreement with results in the mouse [24] and Lewis rats, where peak expression of PER2 occurred in the early part of the dark phase [5]. …”
Section: Discussionsupporting
confidence: 92%
“…The expression of circadian rhythms in physiology and behavior involves the participation of the circadian timing system and includes forebrain structures and the cerebellum [3], subordinate oscillators which, in normal conditions, can express different patterns of clock genes in close phase or in antiphase with the SCN rhythms [4,5]. …”
Section: Introductionmentioning
confidence: 99%
“…Generally, we find very high concordance between rhythms in BA11 and BA47. This is interesting because studies in rodents have suggested that there can be differences in phase between adjacent brain regions (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there are rhythms of PER2 expression in the forebrain, most of which peak near dawn or dusk [17]. As one indication of the important regional heterogeneity in the mammalian forebrain, a second study by this group showed that the expression of Per2, Bmal1 and Dbp mRNA oscillates, with the phase and amplitude of rhythms of each gene, varying across forebrain regions [18]. Presumably these regional differences ensure that the timing of specific behaviors occur at appropriate times of day.…”
Section: Overview Of the Circadian Timing Systemmentioning
confidence: 99%